(untitled) (Journal of Pathology of Nepal, 2020)
Ghost cell odontogenic carcinoma (GCOC) a rare malignant Odontogenic Carcinoma with an unpredictable behaviour presenting with local recurrences and distant metastases, to best of our knowledge about 38 cases have been reported in the past. This is an additional case of GCOC in a 25-year old female presented with a slow-growing mandibular swelling since 9 months with restricted jaw mobility. The CT scan showed an ill-defined osteodestructive lesion in the mandible. The histological examination confirms the diagnoses as a GCOC. Immunohistochemical examination was performed for Ki-67 proliferation index and p53 a predictor of progression. This case was managed by wide surgical resection of tumor and reconstruction of the defect by free fibular flap. Six months follow- up period shows no signs of recurrence. GCOC is rare Odontogenic Carcinoma with unpredictable behaviour however p53 & Ki67 proliferation index can predict the progression of tumor and help in differentiation from benign precursor lesions as early diagnosis & treatment of GCOC is necessary to prevent local recurrences & distant metastases.